Effect of dietary methionine and its analogs on oxidant/antioxidant status of blood and liver in broilers under normal condition or environmental stress: A systematic review and meta-analysis - Hossein Hassanpour; Leila Nasiri; Aziz A. Fallah; Behnam Ahmadipour; Waranyoo Kaewduangta (Journal of Agriculture and Food Research)
This meta-analysis aimed to consolidate the effects of dietary methionine and its analogs on broilers' oxidant/antioxidant status in the blood and liver. A comprehensive search of electronic databases identified 15 studies that met the requirements for a meta-analysis. The meta-analysis was conducted using a random-effects model, and the effect size was calculated as the standardized mean difference with 95 % confidence intervals. Heterogeneity was evaluated using the Cochrane Q test and I2 statistics. The meta-analysis revealed that methionine supplementation significantly reduced oxidative stress markers, such as malondialdehyde (MDA)and protein carbonyl PC, and increased antioxidant parameters, including glutathione (GSH), glutathione disulfide (GSSG), and glutathione peroxidase (GPX). The meta-analysis found significant increases in GSH and GPX levels across two methionine source subgroups, while MDA and PC levels decreased only in the methionine analogs group. GSSG levels were elevated specifically in the DL-/L-methionine group, with no change in TAC (total antioxidant capacity) levels. In terms of challenge type, GSH and GPX levels rose significantly in both normal and environmental stress conditions, while MDA decreased; however, SOD, GSSG, and TAC levels remained unchanged. The analysis of methionine dosage showed that GSH increased in both ≤2.5 and 2.6–4 fold subgroups, while SOD only increased in the ≤2.5 fold subgroup. Lastly, the administration period analysis indicated increases in GPX and GSH for both 1–21 and 22–42 days, with PC levels decreasing. The study also found that methionine supplementation can be an effective strategy to reduce oxidative stress and enhance antioxidant defenses in broilers, particularly under environmental stress conditions. The results suggest that methionine supplementation can be a valuable tool for reducing oxidative stress and improving the overall health of broilers.